Feminism Paradigm In Gender Equality Argument of Nasaruddin Umar - Fata, Ahmad Khoirul; Iderus, Muhammad Hasan Said (KALAM, 2018)
The idea of gender equality, that dominates contemporary men-women relation discourse, makes a number of Muslim thinkers trying to reinterpretation some of the religious doctrines that are considered as biased. At this point the scripture became the main target of the review, because of its position as a major source of religious doctrines. This effort has been done by Nasaruddin Umar through the book "Argument Kesetaraan Gender Perspektif al-Qur'an". By using the hermeneutics and semantics methods, his study focused on the historical study of Arab society and the meaning of vocabulary in the Qur'an that are directly related to gender issues. Nasaruddin saw the primary mission of the Qur’an is actually a liberating womens from the Arab patriarchist and similarity to the relations between men and women. But, the structure of the language and culture of Arab societies have been "trapped" word of God. Its makes a misunderstood that Islam helped to perpetuate the culture. This paper attempts to prove the strong influence of feminism paradigm in the Nasaruddin’s thought, and that so impressed coercion meaning of vocabulary and verses of the Qur’an adapted to the paradigm. The imposition of meaning occurs on the distinction of the meaning of the word al-Rijal / rajul and al-dzakar. The first emphasis on the quality and culture, the second emphasis on the biological aspects. But unfortunately, Nasaruddin was inconsistent using the sense that it provides itself. In addition, this paper provides a critical assessment of his socio-historical approach to build gender equality argument. Here the author found the reckless of Nasaruddin in seeing the socio-historical context of Arab society before and during the revelation of al-Qur'an. This makes his analysis tend to amplify and redirect the reason feminism espoused.